2003
DOI: 10.1046/j.1365-2141.2003.04622.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible regulation of Wilms’ tumour gene 1 (WT1) expression by the paired box genes PAX2 and PAX8 and by the haematopoietic transcription factor GATA‐1 in human acute myeloid leukaemias

Abstract: Summary. Overexpression of the embryonic transcription factor, Wilms' tumour protein 1 (WT1), is common in acute myeloid leukaemias (AML). Mutations of Wilms' tumour gene 1 (WT1) in AML are rare and WT1 expression may be increased by other transcription factors. PAX2, PAX8 and GATA-1 are known physiological regulators of WT1. In the present study, we analysed either bone marrow or blood samples of 43 AML patients for the expression levels of WT1, PAX2, PAX8 and GATA-1 by real-time reverse transcription polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Upon repeated analysis, WT1 levels have remained low and in the same range as levels detected in the bone marrow of healthy subjects. 7 Potential side effects of vaccination with WT1 are of concern due to the low-level expression of WT1 in the kidney, and transiently during maturation in normal hematopoietic progenitor cells. 9 There are, however, several preclinical and clinical studies showing WT1-specific immunity in the absence of autoimmunity (reviewed in Rosenfeld et al 1 and Scheibenbogen et al 10 ).…”
Section: To the Editormentioning
confidence: 99%
“…Upon repeated analysis, WT1 levels have remained low and in the same range as levels detected in the bone marrow of healthy subjects. 7 Potential side effects of vaccination with WT1 are of concern due to the low-level expression of WT1 in the kidney, and transiently during maturation in normal hematopoietic progenitor cells. 9 There are, however, several preclinical and clinical studies showing WT1-specific immunity in the absence of autoimmunity (reviewed in Rosenfeld et al 1 and Scheibenbogen et al 10 ).…”
Section: To the Editormentioning
confidence: 99%
“…16 To date, in addition to Sp1 and GATA-1, PAX2 and PAX8 are also reported to be the transcription factors that regulate WT1 gene expression. [17][18][19][20] Dehbi et al 17 reported the binding sites of PAX2 and PAX8 in the 5 0 promoter of WT1 gene. Zhang et al 20 indicated the importance of the intron 3 enhancer of WT1 gene, which was activated by GATA-1 and Myb.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5 A possible imbalance in the ratio of the main WT1 isoforms in acute leukemia and its effect will require further investigation. 47,48 The WT1 protein possesses immunogenic properties and has been successfully tested as a target for antileukemic vaccines. 2,5,[49][50][51][52][53] The discrepancies between different authors and studies on the expression and role of WT1 in acute leukemia may result from the nonstandardized techniques of WT1 detection and quantification employed (qualitative PCR vs real-time quantitative PCR (RQ-PCR), relative vs absolute methods of the gene expression quantification, different control genes, type and number of negative/normal controls), the type of samples evaluated (bone marrow (BM) vs peripheral blood (PB)), as well as the size and character of the patient groups examined.…”
Section: Introductionmentioning
confidence: 99%